Structural properties and anti-dermatitis effects of flavonoids-loaded gold nanoparticles prepared by Eupatorium japonicum - Xu, Xing Yue; Moon, Sung-Kwon; Kim, Jin-Kyu; Kim, Woo Jung; Kim, Yeon-Ju; Kim, Hoon (Frontiers in Pharmacology, 2022)
Recently, green synthesis-based nanoformulations using plants or microorganisms have attracted great interest because of their several advantages. Nanotechnology-based biological macromolecules are emerging materials with potential applications in cosmetics and medications for ameliorating and treating inflammatory skin diseases (ISDs). Eupatorium japonicum (EJ), a native Korean medicinal plant belonging to the family Asteraceae, has been traditionally used to prepare prescriptions for the treatment of various inflammatory diseases. EJ-based gold nanoparticles (EJ-AuNPs) were biosynthesized under optimal conditions and characterized their physicochemical properties using various microscopic and spectrometric techniques. Additionally, the effects of EJ-AuNPs on ISDs as well as their underlying mechanisms were investigated in the tumor necrosis factor-α/interferon-γ (T+I)-induced skin HaCaT keratinocytes. The MTT and live/dead cell staining assays showed that EJ-AuNP treatment was considerably safer than EJ treatment alone in HaCaT cells. Moreover, EJ-AuNP treatment effectively suppressed the production of T+I-stimulated inflammatory cytokines (RANTES, TARC, CTACK, IL-6, and IL-8) and intracellular reactive oxygen species, and such EJ-driven anti-inflammatory effects were shown to be associated with the downregulation of intracellular mitogen-activated protein kinase and nuclear factor-κB signaling pathways. The present study provides preliminary results and a valuable strategy for developing novel anti-skin dermatitis drug candidates using plant extract-based gold nanoparticles.